2006
DOI: 10.1135/cccc20061088
|View full text |Cite
|
Sign up to set email alerts
|

Purine and Pyrimidine Nucleoside Analogs of 3'-C-Methyladenosine as Antitumor Agents

Abstract: 3'-C-Methyladenosine (3'-Me-Ado) is a mechanism-based ribonucleotide reductase inhibitor endowed with antitumor activity against both human leukemia and carcinoma cell lines. In this paper, we report the synthesis and antitumor evaluation of a series of purine and pyrimidine 3'-C-methylribonucleoside analogs of 3'-Me-Ado. A stereoselective synthesis of the arabino analog of 3'-Me-Ado is also described. Among the tested compounds, only 3'-C-methyluridine showed moderate antitumor activity against human myelogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…18,19 Our previous work on RR inhibitors included the synthesis of 3 0 -C-methyladenosine (3 0 -Me-Ado), a purine ribonucleoside that acts as a mechanism-based inhibitor of the R1 subunit of mammalian RR, and is endowed with significant antitumor activity against a panel of human leukemia and carcinoma cell lines. [20][21][22][23] Interestingly, we found that its cytotoxic and apoptotic activity could be enhanced by combining it with several hydroxamic acid-derived HDAC inhibitors, including the two recently synthesized molecules, MC1864 and MC1879, and the reference compound trichostatin A (TSA). 24 Based on this finding our original aim was to combine 3 0 -Me-Ado with VPA to create a prodrug that would simultaneously deliver both agents into cancer cells for synergistic antitumor activity.…”
Section: B S T R a C Tmentioning
confidence: 98%
See 1 more Smart Citation
“…18,19 Our previous work on RR inhibitors included the synthesis of 3 0 -C-methyladenosine (3 0 -Me-Ado), a purine ribonucleoside that acts as a mechanism-based inhibitor of the R1 subunit of mammalian RR, and is endowed with significant antitumor activity against a panel of human leukemia and carcinoma cell lines. [20][21][22][23] Interestingly, we found that its cytotoxic and apoptotic activity could be enhanced by combining it with several hydroxamic acid-derived HDAC inhibitors, including the two recently synthesized molecules, MC1864 and MC1879, and the reference compound trichostatin A (TSA). 24 Based on this finding our original aim was to combine 3 0 -Me-Ado with VPA to create a prodrug that would simultaneously deliver both agents into cancer cells for synergistic antitumor activity.…”
Section: B S T R a C Tmentioning
confidence: 98%
“…21,30 The disappearance of the nucleosides was monitored by the HPLC-DAD-ESI-MS method. In buffer solution, compounds A157, A160 and A167 were extremely stable (t 1/2 >72 h for all tested compounds, data not shown).…”
Section: B S T R a C Tmentioning
confidence: 99%
“…The synthetic method of displacement of the chlorine atom in the protected ribofuranosides 21 and 22 with the appropriate amines, followed by sugar deblocking in basic conditions, as previously reported by us [9b], was unsuccessful in the case of compounds 9e14, 16 and 17. Therefore, in the first step, [15] were deprotected with methanolic ammonia at low temperature to give compounds 23 and 24; then, in the second step, 6-chlorine atom was displaced by the appropriate amines at r.t. or 40 C, in a 1:1 (v/v) mixture of ethanol and water, to provide the corresponding ribonucleoside analogues 9e14, 16 and 17 in good yields (Scheme 2). Compounds 12 and 17 required a longer reaction time and higher temperature presumably due to the low reactivity of the used amines.…”
Section: Chemistrymentioning
confidence: 99%
“…Compound 7 has been previously reported [13] but any experimental conditions, analytical data and biological evaluation were missed. N 6 -substituted 3 0 -C-methyladenosine derivatives 9e14, 16 and 17 were synthesized by reacting either 6-chloro-(23) [14] or 2-amino-6-chloro-purine-3 0 -C-methylriboside (24) [15] with hydrazine, hydroxylamine, O-methylhydroxylamine or N,O-dimethylhydroxylamine. The synthetic method of displacement of the chlorine atom in the protected ribofuranosides 21 and 22 with the appropriate amines, followed by sugar deblocking in basic conditions, as previously reported by us [9b], was unsuccessful in the case of compounds 9e14, 16 and 17.…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation